Experimental study of pin finned receiver tubes for a parabolic trough solar air collector. (1st September 2020) - Zhao, Ziwei; Bai, Fengwu; Zhang, Xiliang; Wang, Zhifeng
Highlights: Parabolic trough air collector (PTAC) was operated with an outlet air temperature above 200 ℃. Performance of PTAC using receiver tubes with and without pin fin were tested. Energy and exergy efficiency of PTAC related to air flow rate and normalized temperature was studied. Receiver tube with pin fin enhances collector efficiency by 8–17%. Beneficial effect of PTAC using pin fin receiver tube was examined. Abstract: Industrial process air heat applications ranging from 70 to 250 ℃ are crucial for the widespread availability of the solar energy. This study evaluated the overall performance of parabolic trough solar air collector with three different receiver tubes for median temperature heat requirements. A smooth receiver tube and two receiver tubes with internally pin fins were tested in the on-site experiments. The solar collector's performance was characterized by energy efficiency, exergy efficiency and thermal–hydraulic efficiency, respectively. Air temperature rise amounted to 266 °C at air flow rate of 93 Nm 3 /h under the solar radiation around 900 W/m 2 . The experimental results revealed that air temperature rise and pressure drop of the internally pin finned tube were significantly higher than those of smooth tube. Over the range of air flow rate investigated, energy efficiency and exergy efficiency in the internally pin finned tube was found to be 10.4–14.5% and 2.55–4.29% higher than those of the smooth tube, respectively. According to the thermal–hydraulic analysis, at low air flow rates, corresponding to applications requiring air at a higher temperature, the solar air collector with internally pin finned tubes yields a better performance. However, at higher air flow rates the pressure drop increased to be even more than the heat gain, solar air collector with smooth tube showed better thermal–hydraulic efficiency. The receiver tubes with internally pin fins will be very beneficial for the design of parabolic trough solar air collectors working at lower air flow rates.